FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KATEKIS RELAWAN DENGAN KOMITMEN SEBAGAI VARIABEL INTERVENING (STUDI KASUS KOMISI KATEKETIK KEUSKUPAN AGUNG JAKARTA) - Hendro Budiyanto (Universitas Mercu Buana, 2019)
This study aims to determine how strong the effect of competency, motivation, commitment on cathecis voluntary performances in Jakarta archbishop dioses integrated either partially or simultaneously. This study was a category of social management research that uses quantitative research methods. The population in this study are all volunteer catechists in the archdiocese parish that covers 8 areas or eight deaneries. The sampling method was done by using cluster sampling and a total sample was 200 respondents. Tehcnic analysis used is path analysis were previously tested with the classical assumtion test. Hypotesis testing using t-test and F test with confidence level of 5%. The result of this study indicate that competency, motivation and commitment significant influence on voluntary cathecis performance either partially or simultaneously, this is partially evidenced by t-test conducted on the four variable mentioned above and shown simultaneously by the F-test was also conducted to the above four variables. But motivation variable wasn’t effect to the performance of voluntary cathecis.